Multi-omic analysis of PBMCs in sepsis reveals widespread cytotoxic dysfunction and an increased population of CD69 expressing naïve CD4+ T cells - Flynn, Joshua; Baird, Anne Marie; Breen, Eamon; Carty, Michael; McNevin, Ciara S.; McDermott, Lisa; Kenny, Elaine M.; Coakley, John Davis; Ryan, Thomas; Doherty, Derek G.; Sheils, Orla (Frontiers in Immunology, 2025)
IntroductionSepsis is responsible for 1 in 5 deaths globally and the majority of those who survive have lasting health issues. A hallmark of sepsis is a deregulated inflammatory response to infection, with leukocytes playing a critical role.MethodsThis study utilised a targeted single-cell multi-omics approach to characterise peripheral blood mononuclear cell (PBMC) populations and their transcriptomic profiles in an Irish cohort of people with (i) sepsis and (ii) bacteraemia without sepsis (defined as clinically significant positive blood culture without sepsis as assessed by the Clinical Microbiology service).ResultsVariable leukocyte distributions were identified, with decreased cytotoxic lymphocytes, including CD8+ T cells, natural killer cells, CD56+ T cells, γδ T cells, mucosal-associated invariant T cells, and increased T helper (Th) cell subsets within sepsis samples. Additionally, PBMCs from sepsis samples displayed an impaired expression profile in effector T cells, resulting in widespread suppression of PBMC cytotoxic activity.DiscussionThese results identify potential mechanisms underlying the functional impairment witnessed in sepsis. Such mechanisms may inform future diagnostic and treatment strategies.